2020
DOI: 10.1016/j.physa.2020.125090
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, flattening the curve, and Benford’s law

Abstract: For many countries attempting to control the fast-rising number of coronavirus cases and deaths, the race is on to “flatten the curve,” since the spread of coronavirus disease 2019 (COVID-19) has taken on pandemic proportions. In the absence of significant control interventions, the curve could be steep, with the number of COVID-19 cases growing exponentially. In fact, this level of proliferation may already be happening, since the number of patients infected in Italy closely follows an exponential trend. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 40 publications
2
40
0
1
Order By: Relevance
“…We must emphasize that the data after 14 December are made public only on weekly basis from this source. As observed from Figure 2 above the epidemic growths in some of the countries naturally follow an exponential family distribution which may be a suspicious that the data may follow Benford Law [9]. The new cases time series for Serbia show a rapid increase in the figures especially after September 2020.…”
Section: Datamentioning
confidence: 74%
See 2 more Smart Citations
“…We must emphasize that the data after 14 December are made public only on weekly basis from this source. As observed from Figure 2 above the epidemic growths in some of the countries naturally follow an exponential family distribution which may be a suspicious that the data may follow Benford Law [9]. The new cases time series for Serbia show a rapid increase in the figures especially after September 2020.…”
Section: Datamentioning
confidence: 74%
“…In their work with the data (up to June 2020), [9] found that in countries where the precautions and interventions were made to control the expansion of the COVID-19 pandemic the reported data satisfied Benford Law. Based on this result and considering the fact that all the Western Balkan countries took measures until quarantine (period that ended in early June) we studied the reported data if they should satisfied Benford Law.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, across the analysed countries, the share of positive tests was similar (see e.g. [ 27 ]), and no significant deviation from expected dynamics was observed by studies applying Benford’s law [ 28 , 29 ], possibly indicating that these data still capture to a reasonable extent the dynamics of the epidemic wave. In addition, the analysed countries were selected based on the fact that they sufficiently met the other model assumptions, e.g.…”
Section: Methodsmentioning
confidence: 81%
“…Análisis como el que aquí se presenta han tenido gran acogida durante la pandemia de COVID-19. Es así como varios estudios han usado la ley de Benford para detectar posibles fraudes en los datos de la pandemia (19,20), establecer las características comunes de los países que no cumplen la ley de Benford (21) e, incluso, usar la distribución de Benford como criterio para definir si hay "aplanamiento" o no de la curva epidémica (22). En todos estos casos, los autores refieren que la objetividad del método es su mayor fortaleza.…”
Section: Discussionunclassified